Concentrated dual-cation electrolyte strategy for aqueous zinc-ion batteries - Zhu, Yunpei; Yin, Jun; Zheng, Xueli; Emwas, Abdul-Hamid; Lei, Yongjiu; Mohammed, Omar F; Cui, Yi; Alshareef, Husam N (Energy & environmental science, 2021)
Rechargeable Zn-ion batteries are highly promising for stationary energy storage because of their low cost and intrinsic safety. However, due to the poor reversibility of Zn anodes and dissolution of oxide cathodes, aqueous Zn-ion batteries encounter rapid performance degradation when operating in conventional low-concentration electrolytes. Herein, we demonstrate that an aqueous Zn 2+ electrolyte using a supporting Na salt at a high concentration is efficient to address these issues without sacrificing the power densities, cycling stability, and safety of zinc-ion batteries. We show that the high-concentration solute minimizes the number of free water molecules and the changes in the electronic state of the electrolyte. A combination of experimental and theoretical investigations reveals that a unique interphase, formed on the Zn anode, enables reversible and uniform Zn plating. Utilizing a cathode of sodium vanadate synthesized through a scalable strategy, the Zn-sodium vanadate battery with the concentrated bi-cation electrolyte shows improved cycling stability, decent rate performance, and low self-discharge. This work provides new insights on electrolyte engineering to achieve high-performance aqueous batteries. A dual-cation concentrated electrolyte has been developed to enable a stable Zn anode and a vanadium-oxide-based cathode for efficient aqueous Zn-ion batteries.